Classes de Reidemeister para coincidências entre secções de um fibrado - Paiva, Thales Fernando Vilamaior (2014)
In this work we study the theory of Reidemeister coincidence classes for coincidences between two sections s; f : B → E de um fibrado q : E → B, both the algebraic treatment by the Reidemeister action and the geometric treatment given by the theory of covering spaces and conjugacy classes of liftings. The existence of a section of a fibration implies the existence of a short exact sequence on the fundamental groups of the spaces... (continue)